The Influence of Motivation and Situational Leadership Style on the Performance of Priority Relationship Managers in the Wealth Management Division of Bank ABC - Widiyanto, Bambang; Lahindah, Laura (Green Publisher Indonesia, 2025)
The competitive landscape of the banking sector, particularly in wealth management, demands high-performing relationship managers to retain affluent clients and drive revenue. Within this context, work motivation and adaptive leadership practices are regarded as crucial factors influencing employee performance. This research explores the impact of work motivation and situational leadership style on the performance of Priority Relationship Managers at Bank ABC’s Wealth Management Division. Using a quantitative approach and the census method, data were collected from 130 employees through structured questionnaires. The analysis employed Exploratory Factor Analysis and multiple linear regression to examine the relationships among variables, both partially and simultaneously. The results show that both work motivation and situational leadership significantly and positively affect employee performance. Situational leadership exhibited a stronger partial influence, while the combined effect of both variables explained 90.7% of the variance in performance. These findings highlight the strategic importance of adaptive leadership and motivational drivers in enhancing productivity, especially in the competitive landscape of priority banking services.